The children of the plague times: the COVID-19 pandemic in two poems by Alexei Bueno - da Fonseca, Leandro Noronha [UNESP] (FapUNIFESP (SciELO), 2024)
Diseases, epidemics, and pandemics have been present both throughout human history and in the literary production of different periods. In an attempt to understand how the recent COVID-19 pandemic is represented, the article analyzes the poems “Matinada da peste” and “As máscaras”, published by the poet from Rio de Janeiro, Alexei Bueno, in the book Decálogo Indigno para os Mortos de 2020 (Bueno, 2020). The study is guided by the thoughts of Candido (2000) and theorists of poetry and other areas of knowledge on the internal (aesthetic) and external (social) aspects that compose literary works. In general terms, “Matinada da peste” contrasts the timelessness of nature with human vulnerability in the face of the virus. “As máscaras” evokes social isolation through the solitary body, using expressions like: “orphaned eyes,” “lips without lips,” “hands without others,” and hoping for a “new tomorrow.” It is concluded that the content and form of the poems analyzed bear evident marks of the health crisis, such as anguish, waiting, the loneliness of isolation, and the hope for better days.
Los hijos del tiempo de la peste: la pandemia de COVID-19 en dos poemas de Alexei Bueno
Os filhos do tempo da peste: a pandemia de COVID-19 em dois poemas de Alexei Bueno
Keywords: Alexei Bueno; contemporary Brazilian poetry; COVID-19; pandemic